1988
DOI: 10.1093/nar/16.3.941
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination of SV4O DNA in COS7 cells occurs with high frequency m a gene dose independent fashion

Abstract: Homologous recombination between microinjected SV40 DNA fragments and endogenous SV40 DNA in COS7 cells was analysed by immunofluorescence staining and DNA blotting. Time course experiments revealed that recombination between the transferred (trans) DNA and the chromosomal DNA occurred about 8 hours after microinjection with high efficiency in a gene dose independent fashion. Deletions of up to 1018 basepairs (bp) within the early or the late SV40 region were efficiently repaired after the transfer of linear b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, no study has demonstrated a correlation between transgene copy number and targeting frequency. This area has not been extensively researched, but at least two studies have positively determined that there appears to be no relationship whatsoever between the number of copies introduced and the efficiency of [32,41]. The inference must be that the initial search for homology does not seem to be the rate-limiting step for targeting.…”
Section: Transgene Copy Numbermentioning
confidence: 99%
“…However, no study has demonstrated a correlation between transgene copy number and targeting frequency. This area has not been extensively researched, but at least two studies have positively determined that there appears to be no relationship whatsoever between the number of copies introduced and the efficiency of [32,41]. The inference must be that the initial search for homology does not seem to be the rate-limiting step for targeting.…”
Section: Transgene Copy Numbermentioning
confidence: 99%
“…Recombination involving <50 bp of homology has been observed in prokaryotes (Albertini et al 1982;Singer et al 1982;Watt et al 1985;Shen and Huang 1986;Whoriskey et al 1987). Recombination involving <30 bp of homology has been observed in S. cerevisiae (Ahn et al 1988), in D. melanogastei embryos (Pont et al 1988), and in cultured mammalian cells (Anderson et al 1984;Rubnitz and Subramani 1984;Ayares et al 1986;Rommerskirch et al 1988).…”
Section: Formation Of Joint Molecules With Short Regions Of Homologymentioning
confidence: 99%
“…Chromosomal recombination in yeast, which is also conservative, is stimulated by double-stranded breaks in a way that can be described by the double-strand-break repair (DSBR) model for homologous recombination (15)(16)(17). Other conservative models do not require double-stranded breaks, but DSBR serves as an appropriate example here because mammalian targeted recombination is stimulated by doublestranded breaks in the vector (4,18). The model predicts that two copies of a homologous sequence pair on either side of a double-stranded break, forming adjacent Holliday junctions.…”
Section: Introductionmentioning
confidence: 99%